Management of Obesity and Nonalcoholic Fatty Liver Disease: A Literature Review - Hashem, Anas; Khalouf, Amani; Acosta, Andres (Seminars in Liver Disease, 2021)
With the recent urbanization and globalization, the adult obesity rate has been increasing, which was paralleled with a dramatic surge in the incidence and prevalence of nonalcoholic fatty liver disease (NAFLD). NAFLD poses a growing threat to human health as it represents the most common cause of chronic liver disease in developed countries. It encompasses a wide spectrum of conditions starting from a build-up of fat in hepatocytes (steatosis), to developing inflammation (steatohepatitis), and reaching up to cirrhosis. It is also associated with higher rates of cardiovascular mortalities. Therefore, proper timely treatment is essential and weight loss remains the cornerstone in the treatment of obesity-related liver diseases. When diet, exercise, and lifestyle changes are not successful, the current recommendation for weight loss includes antiobesity medications and bariatric endoscopic and surgical interventions. These interventions have shown to result in significant weight loss and improve liver steatosis and fibrosis. In the current literature review, we highlight the expected outcomes and side effects of the currently existing options to have a weight-centric NAFLD approach.
Keywords: nonalcoholic fatty liver disease; nonalcoholic steatohepatitis; obesity; weight loss; bariatric surgery